Concomitant Sigmoid Diverticulitis and Periampullary Duodenal Diverticulitis Complicated by Lemmel Syndrome: A Case Report - Bibek Saha MD; Samuel Jang MD; Joelle N. Friesen MD; Victoria Kalinoski-DuBose MD; Anjul Verma MBBS; William Mundell MD (SAGE Publishing, 2024)
Diverticular disease is a major cause of hospitalizations, especially in the elderly. Although diverticulosis and its complications predominately affect the colon, the formation of diverticula in the small intestine, most commonly in the duodenum, is well characterized in the literature. Although small bowel diverticula are typically asymptomatic, and diagnosed incidentally, a complication of periampullary duodenal diverticulum is Lemmel syndrome. Lemmel syndrome is an extremely rare condition whereby periampullary duodenal diverticula, most commonly without diverticulitis, leads to obstruction of the common bile duct due to mass effect and associated complications including acute cholangitis and pancreatitis. Here, we present the first case, to our knowledge, of periampullary duodenal diverticulitis complicated by Lemmel syndrome with concomitant colonic diverticulitis with colovesical fistula. Our case and literature review emphasizes that Lemmel syndrome can present with or without suggestions of obstructive jaundice and can most often be managed conservatively if caught early, except in the setting of emergent complications.